2007
DOI: 10.1590/s0103-97332007000600018
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diffusion of pions at RHIC

Abstract: After pointing out the difference between normal and anomalous diffusion, we consider a hadron resonance cascade (HRC) model simulation for particle emission at RHIC and point out that rescattering in an expanding hadron resonance gas leads to a heavy tail in the source distribution. The results are compared to recent PHENIX measurements of the tail of the particle emitting source in Au+Au collisions at RHIC. In this context, we show how can one distinguish experimentally the anomalous diffusion of hadrons fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 24 publications
1
45
0
2
Order By: Relevance
“…In an expandig system, the mean free path is increasing as the system expands. In such case a generalized form of the central limit theorem leads to the appearance of the Lévy distribution as source function [4][5][6]. The one-dimensional, symmetric Lévy distribution is defined by a Fourier transform:…”
Section: Two-particle Correlation Functions and The Lévy Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an expandig system, the mean free path is increasing as the system expands. In such case a generalized form of the central limit theorem leads to the appearance of the Lévy distribution as source function [4][5][6]. The one-dimensional, symmetric Lévy distribution is defined by a Fourier transform:…”
Section: Two-particle Correlation Functions and The Lévy Distributionmentioning
confidence: 99%
“…Moreover, it could be associated to one of the critical exponents namely to the critical exponent of the spatial correlation in 3 dimension [4]. Because of this possible relation between the two exponents, the measurements of α could help to locate the critical point on the phase diagram of the QCD if there is any [4,6,18]. The critical exponent of the spatial correlation could vary near to a critical point.…”
Section: Two-particle Correlation Functions and The Lévy Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous years, Gaussian-type sources were usually utilized to describe the correlation functions, but the latest results from the PHENIX experiment showed that we can and have to go beyond the Gaussian approximation [6,7]. In an expanding medium, on the basis of the generalized central limit theorem and the anomalous diffusion we can expect the appearance of Lévy-type sources [8,9]. The symmetric Lévy distribution is the generalization of the Gaussian distribution and it is defined by the following expression:…”
Section: Introductionmentioning
confidence: 99%
“…This may be connected to the non-applicability of the central limit theorem, and the appearance of anomalous diffusion, resulting in a Lévy type of distributions [12,[15][16][17]. These can be expressed as…”
Section: Introductionmentioning
confidence: 99%